The Influence of Competency on the Performance of Civil Servants at the Makassar City Regional Civil Service Agency - Rahmadani; Ilham A. Fattah (GoodWill Journal of Economics, Management, and Accounting, 2025)
This study was conducted at the Regional Civil Service Agency (Badan Kepegawaian Daerah) of Makassar City, located at Jalan Jenderal Ahmad Yani No. 2, Makassar, South Sulawesi Province, Indonesia. The research was carried out over a two-month period, from January to February 2016, consisting of one month dedicated to data collection and one month for data processing and analysis. The purpose of this study was to analyze and evaluate the condition and performance of civil servants (PNS) at the Makassar City Regional Civil Service Agency, particularly in relation to various administrative and human resource management aspects. The research population included all civil servants employed at the agency in the year 2015. A total population sampling technique was employed, involving all 44 civil servants as the research respondents. The method applied in this study was a descriptive quantitative approach, supported by primary data collected through questionnaires and documentation techniques. Data were analyzed using statistical methods to provide an objective description of the characteristics and performance of the respondents. The findings of this study are expected to contribute valuable insights regarding the management of human resources within regional government institutions, particularly in improving the effectiveness and efficiency of civil service performance. Furthermore, the results may serve as a reference for policymakers in formulating strategies related to employee development and organizational improvement. This research also emphasizes the importance of data-driven decision-making processes in enhancing public service quality at the local government level.